Predisposing factors and Prevalence of Urinary Tract Infection in Patients with Acute Coronary Syndrome Undergone Percutaneous Coronary Intervention: Evaluating the Effect on Outcome: Urinary Tract Infection in Acute Coronary Syndrome - Tumrani, Rukhsana; Khan, Muhammad Durrab; Hussain, Syed Atif; Usman, Muhammad; Nigar, Afsheen (Pakistan Journal of Health Sciences, 2024)
The connection between acute infections and acute cardiovascular events was gaining more attention. There was limited research regarding the incidence and impact of Urinary Tract Infection (UTI) in patients undergoing Percutaneous Coronary Intervention (PCI). Objective: To determine the prevalence and risk factors of urinary tract infection in patients with Acute Coronary Syndrome (ACS) undergone PCI and to determine the effect on outcome. Methods: Cross-sectional study conducted in department of cardiology and pathology, Sheikh Zayed Hospital, Rahim Yar Khan from January 2021 to November 2023. ACS patients aged between 25 to 85 years both genders undergone PCI were included. Patients diagnosed with malignant tumor, cardiogenic shock and pregnant females were excluded. All study subjects grouped on the basis of presence and absence of UTI. Outcome studied were bleeding during hospital stay, in-hospital re infarction, atrial fibrillation and Congestive Cardiac Failure (CCF) after procedure. Results: Mean age of study subjects was 48±9.023years with 207(57.98%) males and 150(42.01%) females. Of the total 357 study subjects, UTI was diagnosed in 102(28.57%) patients. Among all patients with UTI, frequency was high among older individuals (n=68) and females (n=58). UTI was associated with higher rate of re-infarction with 40 patients affected among the total 55 patients with re-infarction. Conclusion: On the basis of this study, it has been concluded that concomitant UTI was frequent in patients undergoing PCI for ACS and associated with advancing age, female gender, responsible for prolonged hospital stay and increased risk of reinfarction.